2020
DOI: 10.3390/su12062467
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Wake Evolution of a 1.5 MW Wind Turbine in a Complex Terrain Wind Farm Based on LiDAR Measurements

Abstract: To study the wake development characteristics of wind farms in complex terrains, two different types of Light Detection and Ranging (LiDAR) were used to conduct the field measurements in a mountain wind farm in Hebei Province, China. Under two different incoming wake conditions, the influence of wind shear, terrain and incoming wind characteristics on the development trend of wake was analyzed. The results showed that the existence of wind shear effect causes asymmetric distribution of wind speed in the wake r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Equation (15) shows the laminar flow for (b = 1) and turbulent flow for (b . 1) for the wind speed inside boundary layers.…”
Section: Mathematical Modeling and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (15) shows the laminar flow for (b = 1) and turbulent flow for (b . 1) for the wind speed inside boundary layers.…”
Section: Mathematical Modeling and Solutionsmentioning
confidence: 99%
“…Rewriting equation (17) with the dimensionless variable h and replacing (y) by (r + H b ) in equation (15) and integration limits across rotor blades between gives the power output as: Where H b represents the wind turbine hub height (m).…”
Section: Mathematical Modeling and Solutionsmentioning
confidence: 99%
“…Winstroth et al measured 3D movement and obtained the deflection of 3.2 MW wind turbine blades using DIC and showed that 3D DIC could be a potential method for monitoring the condition of wind turbine blades [22]. Zhao et al measured the fullfield displacement of the blades of a 1.5 MW wind turbine using a system of three stereo cameras [23]. Carr et al performed dynamic tests on wind turbine blades and obtained the corresponding full-field strain measurements using DIC [24].…”
Section: Introductionmentioning
confidence: 99%
“…Literature [5] used two LiDARs to study the three-dimensional wake characteristics of a 1.5 MW wind turbine and verified the wake model. Literature [6] adopted two LiDARs to research the development trend of wake in mountainous terrain.…”
Section: Introductionmentioning
confidence: 99%